Clinical outcomes after surgical or transcatheter aortic valve replacement in patients with chronic kidney disease: an analysis in 29 893 patients from the German Aortic Valve Registry. (25th November 2020) - Mas-Peiro, S; Faerber, G; Bauer, T; Bleiziffer, S; Bekeredjian, R; Boening, A; Frerker, C; Beckmann, A; Moellmann, H; Vasa-Nicotera, M; Ensminger, S; Hamm, C.W; et al.
Abstract: Background: Chronic kidney disease (CKD) is a key risk factor in patients undergoing transcatheter aortic valve implantation (TAVI) or surgical aortic valve replacement (SAVR). Purpose: We analyzed the impact of eGFR and different stages of chronic kidney disease (CKD), on short- and mid-term survival in patients undergoing TAVI or SAVR. Methods: Data from 29893 patients enrolled in the German Aortic Valve registry (GARY) from January 2011 to December 2015 receiving TAVI (n=12834) or SAVR (n=17059) at 88 sites were included. The impact of renal impairment, as measured by eGFR and CKD stages, was investigated. The primary endpoint was 1-year cumulative all-cause mortality. A propensity score method was used to compare TAVI vs. SAVR in patients with intermediate risk and mild-to-moderate renal disease being eligible for both therapies. Results: Higher CKD stages were significantly associated to lower in-hospital, 30-day- and 1-year survival rates. Both TAVI- and SAVR-treated patients in CKD 3a, 3b, 4, and 5 stages showed significant and gradually increasing HR values for 1-year all-cause mortality. The same trend persisted in multivariable analysis, although HR values for CKD 3a and 5 did not reach significance in TAVI patients, whereas CKD 4+5 did not reach statistical significance in SAVR. Likewise, eGFR as a continuous variable was a significant predictor for 1-year mortality, with the best cut-off points being 47.4 mL/min/1.73 m 2 for TAVI and 59.8 mL/min/1.73 m 2 for SAVR. Significant 8.6% and 9.0% increases in 1-year mortality were observed for every 5-mL reduction in eGFR for TAVI and SAVR, respectively. No significant differences in survival were found between TAVI and SAVR in a matched group of intermediate-risk patients potentially eligible for both therapies (HR [(95% CI] for TAVI vs SAVR 1.24 [0.76, 2.02], p=0.240). Conclusions: CKD≥3b and CKD≥3a is an independent major risk factor for mortality in patients undergoing TAVI and SAVR, respectively. In the overall population of patients with severe aortic stenosis, an appropriate stratification based on CKD substage may contribute to a better selection of patients suitable for such therapies. TAVI and SAVR appear to achieve similar survival rates in intermediate-risk patients with moderate-to-severe renal dysfunction. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Unrestricted grants by medical device companies (Edwards Lifesciences, JenaValve Technology, Medtronic, Sorin, St. Jude Medical, Symetis S.A.). Unrestricted support by funding statisticians by the DZHK (Deutsches Zentrum für Herz-Kreislaufforschung).